Post-Delamination Structural Investigation of YBCO Superconducting Tape - Jewell, Matthew C.; Hopp, Christopher; Olson, Tanner; Berger, Kasey (My University, 2017)
YBa2Cu3O7 (YBCO) is a rare-earth based superconductor that is fabricated as a composite tape. Its properties make it a candidate for usage in high-field magnets at cryogenic temperatures. The structure of the tape includes a YBCO superconducting layer, a substrate layer for mechanical strength and texturing, copper and silver layers for protection and electrical performance, and a collection of oxide layers for correct growth of the superconductor (described in more detail below).The composite tape can delaminate internally within layers of the tape under applied stress, so understanding where and why this damage occurs is the focus of this project in order to improve its performance.
Color poster with text, images, tables, and maps.
Keywords: YBCO; Rare-earth cuprate-based superconductors; Superconductors; Posters